Aryl hydrocarbon receptor and aryl hydrocarbon nuclear translocator expression in human and rat placentas and transcription activity in human trophoblast cultures - Stejskalova, Lucie; Vecerova, Lenka; Peréz, Laura Mesa; Vrzal, Radim; Dvorak, Zdenek; Nachtigal, Petr; Pavek, Petr (Toxicological sciences, 2011)
Aryl hydrocarbon receptor (AHR) and its heterodimer aryl hydrocarbon nuclear translocator (ARNT) form a ligand-activated transcription complex that regulates expression of the AHR battery of target genes that includes the most important placental biotransformation enzyme cytochrome CYP1A1. Expression, placental localization, and ontogeny of AHR/Ahr and ARNT/Arnt have not been systematically studied in either human or rat placentas. Moreover, induction of such AHR target genes as CYP1A1, CYP1A2, CYP1B1, UGT1A1, and breast cancer resistance protein (BCRP), as well as of AHR, ARNT, and aryl hydrocarbon receptor repressor (AHRR) genes, after exposure to AHR ligands have not been studied in human placental trophoblast cultures. In this article, we show that only CYP1A1 messenger RNA (mRNA), but not CYP1A2, CYP1B1, UGT1A1, BCRP, AHR, ARNT, and AHRR mRNAs, is significantly induced in human term placental trophoblast cultures after exposure to prototype AHR ligands/activators 2,3,7,8-tetrachlorodibenzo-p-dioxin, 3-methylcholanthrene, omeprazole, and β-naphthoflavone. We localized AHR/Ahr and ARNT/Arnt in rat placental trophoblasts throughout gestation and in first trimester and term human placental trophoblast, which comprise the crucial component of the maternal-fetal barrier. We demonstrate that rat Ahr and Cyp1a1 reached highest expression during gestation days 15 and 18, which might indicate different response to Ahr ligands in placental Cyp1a1 induction during rat gestation. We also propose the JEG3 choriocarcinoma cell line as a cellular model for human trophoblast induction studies through AHR. In conclusion, we describe expression and ontogeny of AHR/Ahr and ARNT/Arnt and systematically characterize induction of major AHR target genes in human placental trophoblast forming the placental maternal-fetal morphological and metabolic barrier.
Keywords: receptory aromatických uhlovodíků; Choriocarcinoma; Transcriptional Activation; vývojová regulace genové exprese; RNA, Messenger; aktivace transkripce; Pregnancy; zvířata; messenger RNA; lidé; ženské pohlaví; trofoblasty; Rats; Aryl Hydrocarbon Hydroxylases; aromatické hydroxylasy; nádorové buněčné linie; Female; Cell Line, Tumor; Gestational Age; Adult; receptory aromatických uhlovodíků - jaderný translokátor; xenobiotika; krysa rodu Rattus; Aryl Hydrocarbon Receptor Nuclear Translocator; Humans; choriokarcinom; Rats, Wistar; Animals; dospělí; Receptors, Aryl Hydrocarbon; Xenobiotics; gestační stáří; těhotenství; Gene Expression Regulation, Developmental; Trophoblasts; potkani Wistar